Visuospatial skills are better predictors than dexterity for basic ultrasonographic and fluoroscopic skills in veterinary students. Issue 1 (4th September 2018) - Walker, Meagan A.; MacCormick, Mathew R.A; Kilkenny, Jessica J.; Phillips, John; Singh, Ameet; zur Linden, Alex
Abstract: Radiological skills including ultrasonography and fluoroscopy, require a combination of manual dexterity and visuospatial skill to develop competency. The ability to detect veterinary students with an interest in radiology but who are deficient in these skills, may permit more individual adaptations to training programs, allowing for students training in radiology to achieve maximal potential. The objective of this cohort study was to investigate whether innate dexterity and visuospatial skill could be used to predict performance of basic ultrasound and fluoroscopic skills in veterinary students. Fifty veterinary students from the Ontario Veterinary College completed three tests of visuospatial ability, two tests of manual dexterity, a three‐dimensional mouse task, an ultrasound skill‐testing task, and a fluoroscopic skill‐testing task. Students who reported chopstick use completed the non‐dominant hand ultrasound task significantly faster than students who did not ( P  = 0.001). There was a significant positive association between scores on the Mental Rotations Test and time to complete the non‐dominant hand ultrasound task ( P  = 0.011) and fluoroscopy task ( P  = 0.029). No variables were associated with time to complete the dominant hand ultrasound task. The results of this study suggest that visuospatial skill, as assessed by the Mental Rotations Test, is a better predictor of baseline ultrasound and endovascular fluoroscopy skill than dexterity, with the exception of reported chopstick use, in veterinary students. Visuospatial skills can be developed and may be useful to include in the veterinary curriculum for students that are deficient, or students entering a field such as diagnostic imaging.